2008
DOI: 10.1038/bmt.2008.195
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing catheter-related infections in the Dutch multicenter study on high-dose chemotherapy followed by peripheral SCT in high-risk breast cancer patients

Abstract: Neutropenia following high-dose chemotherapy leads to a high incidence of infectious complications, of which central venous catheter-related infections predominate. Catheter-related infections and associated risk factors in 392 patients participating in a randomized adjuvant breast cancer trial and assigned to receive high-dose chemotherapy and peripheral stem-cell reinfusion were evaluated. Median catheter dwell time was 25 days (range 1-141). Catheter-related infections were seen in 28.3% of patients (11 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(46 reference statements)
0
3
1
4
Order By: Relevance
“…Neutropenia is a known risk factor for GNB [25–28]. However, in this current study, we found that neutropenia was independently associated with non‐CRBSIs.…”
Section: Discussioncontrasting
confidence: 70%
“…Neutropenia is a known risk factor for GNB [25–28]. However, in this current study, we found that neutropenia was independently associated with non‐CRBSIs.…”
Section: Discussioncontrasting
confidence: 70%
“…Outro estudo evidenciou que o tempo de neutropenia anterior à enxertia das CTH é um fator preditivo para ocorrência de infecção 24 . Outros autores discutem que a neutropenia constitui uma das fases mais preocupantes, durante a qual as medidas relativas à prevenção de infecção são fundamentalmente imprescindíveis para o desfecho favorável do tratamento 25 .…”
Section: Metodologiaunclassified
“…as condições clínicas do paciente podem ser preditoras do aparecimento de infecções relacionadas ao cateter, assim como o quadro de neutropenia acima de 10 dias, associado ao uso do cateter para infusão de altas doses de quimioterápicos e de nutrição parenteral total (nPt) 9 . dessa forma, considera-se de extrema relevância que os enfermeiros e demais profissionais da saúde, responsáveis diariamente pelo manuseio do cateter venoso central, tenham o conhecimento acerca das principais complicações que levam à retirada desse dispositivo, para que possam planejar e implementar ações que garantam sua permanência e minimizem os riscos para os pacientes.…”
Section: Introductionunclassified
“…ressalta-se que, dos 36 pacientes que receberam nPt, na maioria das vezes em função do desenvolvimento de mucosite, 44,4% tiveram alguma infecção relacionada ao cateter. nesse sentido, a literatura aponta relação importante da ocorrência de infecções de cateter com o uso de acessos venosos semi-implantados para administração de nPt 9 .…”
Section: Introductionunclassified